Multisystemic Increment of Cortical Thickness in Congenital Blind Children. Issue 1 (9th October 2020) - Inuggi, Alberto; Pichiecchio, Anna; Ciacchini, Benedetta; Signorini, Sabrina; Morelli, Federica; Gori, Monica
Abstract: It has been shown that the total or partial lack of visual experience is associated with a plastic reorganization at the brain level, more prominent in congenital blind. Cortical thickness (CT) studies, to date involving only adult subjects, showed that only congenital blind have a thicker cortex than age-matched sighted population while late blind do not. This was explained as a deviation from the physiological mechanism of initial neural growth followed by a pruning mechanism that, in congenital blind children, might be reduced by their visual deprivation, thus determining a thicker cortex. Since those studies involved only adults, it is unknown when these changes may appear and whether they are related to impairment degree. To address this question, we compared the CT among 28 children, from 2 to 12 years, with congenital visual impairments of different degree and an age-matched sighted population. Vertex-wise analysis showed that blind children, but not low vision one, had a thicker cortical surface in few clusters located in occipital, superior parietal, anterior-cingular, orbito-frontal, and mesial precentral regions. Our data suggest that the effect of visual impairment on determining thicker cortex is an early phenomenon, is multisystemic, and occurs only when blindness is almost complete.